Carte reduite des parties connues du globe terrestre : dresseÌe au deÌpost des Cartes Plans et Journaux de la Marine. - Bellin, Jacques Nicolas, 1703-1772 ([DeÌpost des Cartes, Plans et Journaux de la Marine], 1755)
Map shows known extent of six continents; western portion of Nouvelle Hollande [Australia], only portions of northwestern coastline of North America, and southern portion of Greenland. Includes text: Avertissement, notes and dates of discovery. Relief shown pictorially. Scale not noted.